ANALISIS DISPARITAS WILAYAH DILIHAT DARI PEREKONOMIAN KABUPATEN/KOTA PROVINSI BALI : PENDEKATAN SIGMA DAN BETA KONVERGEN - Juliarta, I Made Guna; Setyari, Ni Putu Wiwin (Buletin Studi Ekonomi; VOL.27.NO.1.FEBRUARI 2022, 2022)
Economic development on the one hand is more oriented towards high economic growth because it can have a direct impact on the real economic sector, it will also have an impact on per capita income, increase consumption and will encourage a better economic structure. As a result of the orientation of high economic growth, it can affect development inequality between regions. This study aims to determine whether there is a decrease in the gap in economic growth every year (convergent sigma) and whether there is an acceleration of economic growth in underdeveloped regions against developed regions (convergent beta) in Bali Province in 2010-2020. By using secondary data and panel data regression analysis. The results of the sigma convergence analysis show that there is a divergence and the analysis of beta convergence does not show the occurrence of convergence of economic growth in districts/cities in the province of Bali. The variabels of Government Expenditure, Investment, and HDI have not been able to encourage convergence.